2017
DOI: 10.4330/wjc.v9.i3.248
|View full text |Cite
|
Sign up to set email alerts
|

Validity of electrocardiographic criteria for increased left ventricular mass in young patients in the general population

Abstract: AIMTo investigate validity of electrocardiographic (ECG) criteria for left ventricular hypertrophy (LVH) in young adults.METHODSRetrospectively, echocardiograms showing LVH and concomitant electrocardiograms were collected in patients 18 to 39 years old. A control group of patients without LVH was collected. Using echocardiogram as the gold standard, electrocardiograms were analyzed using common voltage criteria.RESULTSStudy included 100 subjects (52% male, mean age = 28 ± 6.8 years, 96% Hispanic or African-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
6
3
Order By: Relevance
“…RaVL criterion in our study was found to have lower sensitivity and specificity than was known from the previous studies [14,15,16]. Cornell voltage and Cornell product criteria were slightly more reliable for diagnosing LVH and had similar sensitivity and specificity as in other studies [14,15,17,18,19]. The reliability of Peguero-Lo Presti criterion to diagnose LVH was not as high as described by the developers of this criterion, but the sensitivity and specificity was not as low as in a study conducted in Japan [14,18].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…RaVL criterion in our study was found to have lower sensitivity and specificity than was known from the previous studies [14,15,16]. Cornell voltage and Cornell product criteria were slightly more reliable for diagnosing LVH and had similar sensitivity and specificity as in other studies [14,15,17,18,19]. The reliability of Peguero-Lo Presti criterion to diagnose LVH was not as high as described by the developers of this criterion, but the sensitivity and specificity was not as low as in a study conducted in Japan [14,18].…”
Section: Discussioncontrasting
confidence: 76%
“…A part of calculated sensitivity and specificity of ECG criteria differed from those that were seen in previous studies. RaVL criterion in our study was found to have lower sensitivity and specificity than was known from the previous studies [14,15,16]. Cornell voltage and Cornell product criteria were slightly more reliable for diagnosing LVH and had similar sensitivity and specificity as in other studies [14,15,17,18,19].…”
Section: Discussioncontrasting
confidence: 54%
“…S wave of greater duration than R wave or greater than 40 ms in leads I and V6. Normal R peak time in leads V5 and V6 but greater than 50 ms in lead V1 [38] Poor R wave progression (PRWP) R-wave in V3 or V4 ≤2 mm [39] Left atrial enlargement (LAE) any one of the following: 1) P wave in any lead > 0.11s, 2) Notched P wave with interpeak duration > 0.04s (P mitrale), 3) P wave axis < 30°, 4) Area of negative P terminal force in lead V1 (NPTF-V1) > 0.04s•mm, or 5) Positive P terminal force in aVL (PPTF-aVL) > 0.5 mm [40] left ventricular hypertrophy (LVH) Sokolow-Lyon voltage criteria: the amplitude of the S wave in lead V1 was added to the largest amplitude of the R wave in either lead V5 or V6, with a value greater than or equal to 35 mm meeting criteria for LVH [41] Right atrial enlargement (RAE) Any one of the following: 1) P wave in inferior leads II, III, aVF > 2.5 mm or 2) Positive P wave in V1 > 1.5 mm [40] Right ventricular hypertrophy (RVH)…”
Section: Availability Of Data and Materialmentioning
confidence: 99%
“…1 According to Sokolow-Lyon voltage criteria,LVH is a total S wave at V2 and R wave in wave V5> 35 mm, and this result supports the patient's diagnosis of congestive heart failure. 10 Green Medical Journal, Vol. 2 No.…”
Section: Publisher: Faculty Of Medicine Universitas Muslim Indonesiamentioning
confidence: 99%